Charged-particle multiplicity dependence of charm-baryon-to-meson ratio in high-energy proton-proton collisions - Chen, Yu; He, Min (Physics letters. B, 2021)
We propose that the charged-particle multiplicity dependence of the charm-baryon-to-meson ratio observed in high-energy pp collisions can be explained by canonical treatment of quantum charges in the statistical hadronization model (SHM). Taking the full particle listings of PDG complemented by additional charm-baryon states from relativistic quark model predictions, we evaluate the canonical partition function and the charm-hadron chemical factors that measure the canonical suppression arising from the requirement of strict conservation of quantum charges. We demonstrate that, while charm number conservation induces common suppression on the production of both charm-baryons and -mesons, baryon (strangeness) number conservation causes further suppression on charm-baryons (charm-strange mesons) relative to nonstrange charm-mesons, thereby resulting in a decreasing Λc/D0 (Ds/D0) ratio toward smaller multiplicity events. The charm-hadron thermal densities thus computed are then used as pertinent weights to perform charm-quark fragmentation simulations yielding pT-dependent Λc/D0 and Ds/D0 ratios at varying multiplicities in fair agreement with ALICE measurements.